2022
DOI: 10.3389/fgene.2022.772143
|View full text |Cite
|
Sign up to set email alerts
|

Gene Spectrum and Clinical Traits of Nine Patients With Oocyte Maturation Arrest

Abstract: Background: Oocyte maturation arrest is a disease that produces immature oocytes and cannot be mature after culturing in vitro, which leads to female primary infertility. We aimed to summarize nine representative patients in our center to retrospectively analyze the genetic variants and clinical characteristics of oocyte maturation arrest.Methods: This study examined and analyzed nine families with oocyte maturation arrest. Whole-exome sequencing (WES) of the probands was performed to detect the pathogenic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The data on pathogenic PATL2 mutants reviewed by Sun et al and reported in a recent study were reanalysed ( Liu et al, 2021 ; Huang et al, 2022 ; Huo et al, 2022 ; Sun et al, 2022 ). A total of 34 patients with OOMD were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data on pathogenic PATL2 mutants reviewed by Sun et al and reported in a recent study were reanalysed ( Liu et al, 2021 ; Huang et al, 2022 ; Huo et al, 2022 ; Sun et al, 2022 ). A total of 34 patients with OOMD were included.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionary conservation of the variants among the species was analysed using ConSurf server ( http://consurftest.tau.ac.il ). The outcome data of the PATL2 pathogenic mutants reported in the literature ( Liu et al, 2021 ; Huang et al, 2022 ; Huo et al, 2022 ; Sun et al, 2022 ) were re-analysed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scientists have been exploring the specific mechanisms of oocyte maturation arrest (OMA) ( 6 ) and have identified several related genes, including TUBB8 ( 7 , 8 ), PATL2 ( 9 , 10 ), TRIP13 ( 11 ), and TBPL2 ( 12 , 13 ). Mutations of these genes could cause OMA at either GV or MI stage.…”
Section: Introductionmentioning
confidence: 99%